2019
DOI: 10.17221/367/2018-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Modern trends in logistics of agricultural enterprises

Abstract: The article is devoted to the analysis of the use of modern trends in the logistics of agricultural enterprises in Slovakia in order to achieve a competitive advantage and to ensure the improvement of the course of business activities. The research was carried out in 67 agricultural enterprises on the territory of Slovakia. The following methods of data collection were used: Computer-Assisted Web Interviewing, Computer-Assisted Telephone Interviewing and Computer-Assisted Personal Interviewing. When interpreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…High-quality storage, deep processing, modern logistics and well-developed infrastructure should become priority projects, since it is they that ensure the delivery of products to the consumer in the most popular form [25]. In [26], researchers emphasize that the need to digitize and transfer big data will lead to better solutions, and, as a result, to increase operational efficiency, reduce costs, risks, flexibility, efficiency and clarity of logistics processes in agricultural enterprises. Accepting Industry 4.0, Slovak enterprises (71.6%) fully agreed with the use of logistics technology.…”
Section: Resultsmentioning
confidence: 99%
“…High-quality storage, deep processing, modern logistics and well-developed infrastructure should become priority projects, since it is they that ensure the delivery of products to the consumer in the most popular form [25]. In [26], researchers emphasize that the need to digitize and transfer big data will lead to better solutions, and, as a result, to increase operational efficiency, reduce costs, risks, flexibility, efficiency and clarity of logistics processes in agricultural enterprises. Accepting Industry 4.0, Slovak enterprises (71.6%) fully agreed with the use of logistics technology.…”
Section: Resultsmentioning
confidence: 99%
“…Businesses must also focus on the environmental side of production [16]. they must consider digitization production and logistics [18].…”
Section: Discussionmentioning
confidence: 99%
“…To be more effective, however, Figure 6 is limited to the industrial sectors that presented at least three application papers. In total, eighteen different industrial sectors were identified in the sample of papers examined; those not shown in Figure 6 are: courier [59,60] agriculture [61,62] and electrical [51,57] -with two papers each; serious games [54], packaging [53], maintenance, repair and operations parts [63], petroleum [57] and jewellery [64] -with only one paper each. From Figure 6 it can be seen that 70 papers do not indicate any specific application field for Logistics 4.0.…”
Section: Descriptive Statisticsmentioning
confidence: 99%